Examining UTAUT model for mobile food ordering applications (MOFAs): A case study of Food-panda application - Uroosa Raees; Syed Afzal Moshadi Shah; Iftikhar Ahmed Khan; Musaddag Elrayah; Abbas N Albarq; Mohamed A. Moustafa; Khaled Al Falah; Jehad A. Afaneh (International Journal of Data and Network Science)
The purpose of the study was to examine the effectiveness of the Mobile Food Ordering Application (MFOA) in a collectivist country like Pakistan. Data was gathered using an online survey-based approach from 354 MFOA users and was analyzed using the structural equation modeling technique through Smart PLS 3.0. The results show that consumers’ online reviews strongly influence customer satisfaction and continued intention. Similarly, price value and online tracking of food services are strongly associated with customer satisfaction. Consumer habits and facilitation conditions are significantly associated with consumer continued intention. Habit is also found to partially mediate consumer satisfaction and continued intention. The study did not find any support for performance expectancy, effort expectancy, social influence, price value, hedonic motivation, or online review with continued intention. Similarly, performance expectancy, effort expectancy, social influence, facilitating conditions, and hedonic motivation were not associated with consumer satisfaction. The present work is the first of its kind that has empirically examined the effectiveness of MFOAs in Pakistan. It lays down useful practical implications for practitioners, policymakers, and academia.